IMPLEMENTASI MODEL PENGUATAN KURIKULUM BERBASIS PESANTREN (STUDI KASUS PADA MADRASAH ALIYAH (MA) DI KUDUS) - Ihsan, Ihsan (QUALITY, 2017)
From political and regulatory viewpoints, the existence of Madrasahs as educational institutions get stronger with the issue of Regulation No. 2 Year 1989 and Regulation No. 20 Year 2003 and their derivative regulations. On the one hand, the regulations have helped facilitate the madrasahs get equal footing with public schools – even to some enjoy equal status  with public schools – and on the other hand, this new position confronts madrasahs with the challenges due to the fact that many of them have inferior resources. Conceptually, this Islamic boarding-based madrasah model is manifestation of divinity based education concept. Technically, this model adopt concept boarding school and/or full-day school. With this model, it is hoped that there will no more limitation of time to offer quality teaching and education. This model will not only let the madrasahs offer formal curriculum but hidden curriculum as well. Departing from the objective realities and the typology of madrasah aliyah in Kudus, the Islamic boarding-based madrasah as a model offered in this study is classified into three different models, i.e. Pesantren (Islamic boarding) madrasah, Pesantren Environment Madrasah, and Pesantren Values System Pesantren. As to implement these models, it is suggested that the madrasah will choose either one of the three which suits best to their contexts and capacities.